Evaluation of a confocal WSI scanner for FISH slide imaging and image analysis - Xiujun Fu (Diagnostic Pathology, 2017)
Background:  Technological advances contribute to the maturation of digital pathology in clinical and research applications. However, there are only few reports on fluorescence scanning especially on confocal fluorescence imaging technology in digital pathology, which has superior depth resolution compared to wide-field fluorescence imaging. Here, we explored the features of a confocal WSI scanner for typical diagnostic and research imaging applications of fluorescence in situ hybridization (FISH) assay.